Preventable death causes contribution to life expectancy in the Valle de Aburra without Medellin (Colombia) - González Arango, Eliana; Grisales Romero, Hugo (Investigación y Educación en Enfermería, 2010)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> Objective. To describe the contribution of preventable death causes to life expectancy in the Valle de Aburra municipalities without Medellin between 1979 and 2004. Methodology. Death causes were classified according to the inventory of Avoidable mortality Causes. For life expectancy calculations and its decomposition, rates were standardized according to DANE’s 2005 Colombian population. Arriaga’s method was followed in life expectancy decomposition. Results. In the Valle de Aburra not including Medellin, life expectancy at birth for the years 1979-2004 was of 73.23 years. 15.30 years of life expectancy were lost for the period between 1979 and 1995, loss being of 12.58 years for the period between 1996 and 2004. It was stressed that preventable death causes related with vaccination in women (0.0105 years) were important for their negative contribution to the gained life expectancy years. Conclusion. Avoidable mortality structure from the Valle de Aburra without Medellin was mainly affected by the vaccination group constituent diseases or preventive treatment. It is necessary to prioritize public health interventions in the diseases with a greater contribution to the to the vaccination groups or preventive treatment to avoid a significantly negative change in the mortality profiles in the municipalities and know how they affect mortality structure by causes and how they define specific mortality profiles.